Activity levels in attention deficit disorder with and without hyperactivity - Abaya, Leah Marave (ProQuest Dissertations & Theses Global, 1998)
"The reinstatement in DSM-IV of an ADHD subtype without hyperactivity has raised the question of whether the lack of hyperactivity in this subtype can be taken a step further, and be defined as hypoactivity instead. To test whether ADD/WO boys were less active than both ADDH boys and normal controls, and whether ADDH boys were more active than both normal and ADD/WO boys, their activity levels were objectively measured using an accelerometer-based monitor while they were off any medication prescribed for the treatment of ADHD symptoms. Using an instrumented measure of activity also addressed the question of whether the hyperactivity of ADDH boys described in the literature mostly in terms of rating scale data could be confirmed by an objective measurement technique. Boys previously diagnosed with either ADDH or ADD/WO by their respective pediatricians or neurologists, and a control group who had never received a diagnosis for either, were recruited through advertisements in parent newspapers and posted flyers in Chicago suburbs. All participants were administered a CPT, and their parents completed a behavior rating scale to confirm diagnostic symptoms of inattention, impulsivity and hyperactivity. Participants wore the Caltrac\sp{\rm TM} activity monitor for all waking hours for 3-5 days, and their parents recorded the data readings daily. Individual mean activity levels were compared among the three diagnostic groups. ADD/WO children did not have lower activity levels than normal controls, and ADDH participants did not have higher activity levels than normal controls. Both ADD/WO and ADDH children were normally active. Parental perceptions of motor excess as indicated by rating scale scores were therefore not confirmed by objective measurement. A possible explanation for this result was that rating scales may not exclusively measure hyperkinesis but include other qualities of behavior that call special attention to those individuals subsequently diagnosed with ADHD. Implications for diagnostic criteria and theoretical models of ADHD are discussed." -- Abstract.